OPTIMASI SEREAL PANGAN DARURAT SUBSITUSI TEPUNG BERAS, MAIZENA, DAN TAPIOKA METODE CRISP DAN FUZZY LINEAR PROGRAMMING - Shalli Shalli Nurhawa (Pasundan Food Technology Journal (PFTJ), 2023)
The purpose of this study was to determine the substitution of rice flour, maizena, and tapioca that used in making cereals product for emergency food. The experimental design used in this study were organoleptic responses which include attributes of color, aroma, taste and texture. The chemical responses used in this study were carbohydrate content, protein content, fat content, water content, ash content, and fiber content. The result showed that the ratio of rice flour, maizena, and tapioca were used for optimized cereal product used in Crisp Linear Programming to determine the highest total calory when the cost material stabil, and Fuzzy Linear Programming used to determine minimal the cost in case the cost of material fluctuated. The result showed that the ratio of rice flour, maizena, and tapioca had an effect on the organoleptic responses, the chemical responses, optimized the highest total calory, optimized the cost in case the cost of material fluctuated, and the determination of product shelf life.